Method: chemical and morphological studying of paraffin sections - Kuzenko Ye.V. (Морфологія, 2014)
Background. Interactions between heavy metals and cells are diverse, but can be divided into 3 major categories: 1) metals are essential for metabolism. Toxic metals can stop metabolic reactions; 2) metals can accumulate in cells: intracellular uptake and binding; 3) metals that undergo biochemical transformation (inclusive of leaching). The main objectives in this study were to develop a appropriate methodology to allow histological sections scanning electron microscopy analysis of tissue samples and to apply this and a number of other analytical techniques, to investigate the nature of calcific and heavy metals deposits in tissues and cells. Objective. Aim of this study was to find if scanning electron microscopy can be used in chemical composition of tissue. Methods. For recognition of various types of tissue paraffin sections and the rate of accumulation of heavy metals in it was used scanning electron microscope equipped with energy dispersive X-ray spectroscope. Results. Energy dispersive X-ray spectroscopy analysis revealed that inorganic phases of tissue paraffin sections were available for chemical analysis. Scanning electron microscopy were used for morphological analysis of paraffin sections. Conclusion. Rationale and description of the new method of chemical and morphological studying of paraffin sections presented in the article. Scanning electron microscope equipped with energy dispersive X-ray spectroscope can be used in chemical composition of tissue. Citation: Kuzenko YeV. Method: chemical and morphological studying of paraffin sections. Morphologia. 2014;8(2):89-92.